2005
DOI: 10.1073/pnas.0506471102
|View full text |Cite
|
Sign up to set email alerts
|

Human C4b-binding protein selectively interacts withNeisseria gonorrhoeaeand results in species-specific infection

Abstract: Neisseria gonorrhoeae is the causative agent of gonorrhea, a disease that is restricted to humans. Complement forms a key arm of the innate immune system that combats gonococcal infections. N. gonorrhoeae uses its outer membrane porin (Por) molecules to bind the classical pathway of complement down-regulatory protein C4b-binding protein (C4bp) to evade killing by human complement. Strains of N. gonorrhoeae that resisted killing by human serum complement were killed by serum from rodent, lagomorph, and primate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 51 publications
5
93
0
1
Order By: Relevance
“…Comparative studies of another member of the Ail family, Rck of S. typhimurium, may suggest that the mode of OmpX action is through inhibition of C9 polymerization and formation of the mature membrane attack complex (MAC) on the bacterial surface (Heffernan et al, 1992b). It has also been reported that Y. pestis binds the complement regulatory protein C4bp as observed by Ngampasutadol et al (2005). Whether Y. pestis OmpX is directly involved in these latter two processes is currently being examined.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies of another member of the Ail family, Rck of S. typhimurium, may suggest that the mode of OmpX action is through inhibition of C9 polymerization and formation of the mature membrane attack complex (MAC) on the bacterial surface (Heffernan et al, 1992b). It has also been reported that Y. pestis binds the complement regulatory protein C4bp as observed by Ngampasutadol et al (2005). Whether Y. pestis OmpX is directly involved in these latter two processes is currently being examined.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously (39). To detect direct bacterial binding of HufH, FHL-1, and FHR-1 and fH from other primates, 10 8 N. gonorrhoeae, were suspended in HBSS 2ϩ and incubated for 30 min at 37°C with 10% (v/v) heat-inactivated NHS or heat-inactivated serum from chimpanzee, baboon, and rhesus in a final reaction volume of 100 l. Bacteria were washed three times in HBSS 2ϩ , followed by digestion of bacterial pellets with 4ϫ lithium dodecyl sulfate sample buffer (NuPAGE LDS sample buffer; Invitrogen Life Technologies).…”
Section: Western Blottingmentioning
confidence: 99%
“…Certain Por1B gonococci can also bind chimpanzee C4BP. These strains also resist killing by normal chimpanzee serum (NChS) (39) and can be used successfully to infect chimpanzees experimentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The antigenic variability is also the major reason why there is still no vaccine against N. gonorrhoeae available. Furthermore, these bacteria also manage to inactivate or delude the complement system of human serum by recruiting the inhibitory complement component C4b-binding protein or by sialylation of their outer membrane lipooligosaccharide with host-derived cytidine 5 0 -monophosphate-N-acetylneuraminic acid (Mandrell and Apicella, 1993;Ngampasutadol et al, 2005;Putten, 1993).…”
Section: Ancestry and Evolution Of Ceacam3mentioning
confidence: 99%